2007
DOI: 10.1007/s12036-007-0003-9
|View full text |Cite
|
Sign up to set email alerts
|

Modeling repulsive gravity with creation

Abstract: There is a growing interest in the cosmologists for theories with negative energy scalar fields and creation, in order to model a repulsive gravity. The classical steady state cosmology proposed by Bondi, Gold and Hoyle in 1948, was the first such theory which used a negative kinetic energy creation field to invoke creation of matter. We emphasize that creation plays very crucial role in cosmology and provides a natural explanation to the various explosive phenomena occurring in local (z < 0.1) and extra galac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…It is worthwhile to mention that the WMAP observations are also consistent with the decelerating model (please refer [45,46] and reference there in).…”
Section: Case Ii: Power Law Relation Between Displacement Field and Hmentioning
confidence: 76%
See 1 more Smart Citation
“…It is worthwhile to mention that the WMAP observations are also consistent with the decelerating model (please refer [45,46] and reference there in).…”
Section: Case Ii: Power Law Relation Between Displacement Field and Hmentioning
confidence: 76%
“…The value of displacement field, energy density, pressure and bulk viscosity can be obtained using (22)-(24), (43)- (46), (49) and (50) as…”
Section: Cosmological Models With Variable Gravitational Constantmentioning
confidence: 99%
“…We do not make any additional assumption of minimal coupling (no interaction) between matter and dark energy (which anyway seems ad-hoc and nothing more than a simplifying assumption) and believe that interaction is more natural and is a fundamental principle (Vishwakarma and Narlikar 2007). This leads to…”
Section: Walker Metricmentioning
confidence: 99%
“…Although, the recent observations favour accelerating models at present but the possibility of decelerating models with small deceleration parameter are not completely ruled out. It has also been shown that the high redshift supernovae Ia can also be explained successfully in the decelerating models if one takes into account the absorption of light by the intergalactic metallic dust ejected from the supernovae explosions (Vishwakarma 2002(Vishwakarma , 2005. In view of this, in the next section we choose the value of β slightly greater than 1, so that the deceleration parameter will be very small close to zero as t → ∞.…”
Section: Models With γ =mentioning
confidence: 99%
“…The best examples were : 1) Existence of atom 2) Existence of quantum of energy 3) Existence of integral nature of angular momentum 4) Existence of wave mechanics 5) Six quarks having fractional charge 6) Confirming the existence of muon/pion 7) Existence of Black holes 8) Black hole radiation 9) Einstein's cosmological Lambda term 10) Cosmic red shift 11) Discovery of CMBR 12) Accelerating universe and Dark energy [1][2][3][4][5][6][7][8][9][10][11]. The evidence for dark energy is only indirect and many things about the nature of dark energy remain matters of speculation.…”
Section: Introductionmentioning
confidence: 99%